2006
DOI: 10.1007/s11111-006-0023-4
|View full text |Cite
|
Sign up to set email alerts
|

Emergy-based Simulation to Assess Brazil’s Long-term Carrying Capacity: Environment, Electricity and Population

Abstract: A macroscopic mini-model of Brazil's electrical generating capacity (BRAZ-ELECTRIX, Brazilian Electricity Matrix) was developed using the Energy Systems Language and simulated with iconographic ExtendÒ software to explore long-term (200 years) population carrying capacity. South American reserves of natural gas (NG) and Brazilian stream hydro-power potential were assumed as the main inputs to electric power production. Energy values (e.g., kWh, joules) for fuels, electricity and environment were transformed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Emergy analysis theory, which can convert all kinds of different categories of energy and matter to the same standard values, was first proposed for quantitative analysis in the 1990s [17]. This theory was widely used to solve the energy unit-inconformity in different nature or social systems; to measure the real value of the natural environment resources and economic activities; to analyze the relationship among components of a complex system, to harmonize ecological protection and economic and social development [18][19][20][21]. In recent decades, there have been many applications of this theory on the input-output analysis of agricultural ecosystems [22,23] to assess the level of social sustainable development [24], dynamic analysis [25,26], scenario forecasting [27].…”
Section: Introductionmentioning
confidence: 99%
“…Emergy analysis theory, which can convert all kinds of different categories of energy and matter to the same standard values, was first proposed for quantitative analysis in the 1990s [17]. This theory was widely used to solve the energy unit-inconformity in different nature or social systems; to measure the real value of the natural environment resources and economic activities; to analyze the relationship among components of a complex system, to harmonize ecological protection and economic and social development [18][19][20][21]. In recent decades, there have been many applications of this theory on the input-output analysis of agricultural ecosystems [22,23] to assess the level of social sustainable development [24], dynamic analysis [25,26], scenario forecasting [27].…”
Section: Introductionmentioning
confidence: 99%
“…In measure of the sustainable development of urban ecosystem, the balance of emergy will be more important. If the output emergy left the local are more than the input, the regional economy is not sustainable [4] . In 2010, the input emergy ( R+F ) of eco-economic system of Hefei city was 2.35×10 22 sej, the output emergy (Y+N) was 1.95×10 22 sej, the surplus emergy was 0.40×10 22 sej, accounting for 17.02% of the applied emergy, which indicated that the emergy of Hefei city continued to increase and accumulate, and this was the real reason of the rapid development of Hefei city in recent years.…”
mentioning
confidence: 99%